When Lightning Strikes the HeartKey PointsClinical QuestionClinical Question - Abiodun Idowu, MD; Indiresha R. Iyer, MD (CHEST Critical Care)
Cloud-to-ground lightning strikes are the second leading cause of weather-related deaths in the United States. Lightning strike injuries are more common in summer months, especially in the southeastern and southern parts of the United States. Deaths resulting from lightning strikes are 4 times more common in male patients. The average age of death is 37 years. Two-thirds of lightning-associated deaths occur in the first hour of injury and generally are the result of cardiorespiratory arrest. Lightning injuries occur through direct strike, indirect strike, side flash, ground current, upward streamers, and blast effects. Postulated mechanisms for cardiovascular damage include electroporation, myocardial hemorrhage and necrosis, contusion, induced electric currents, catecholaminergic surge, coronary vasospasm, blast injury, and corticomedullary brain dysfunction. Clinical cardiac manifestations include asystole; ventricular and atrial arrhythmias; hypotension; ventricular dysfunction; cardiomyopathy; cardiogenic shock; dynamic ST-segment and T-wave ECG changes, including ST-segment elevation myocardial infarction pattern; pericardial effusion; tamponade; and aortic injury. Immediate, sustained, and aggressive resuscitation efforts, so-called reverse triage, and rapid transportation to hospitals, even with prolonged asystole, often lead to complete recovery. Among hospitalized patients, cardiac arrest, ventricular arrhythmias, and an ECG pattern of ST-segment elevation myocardial infarction are associated with increased odds of mortality. Standard trauma, burn, and advanced cardiac life support protocols are recommended for management. Technological advances in weather forecasting, public awareness, and policies related to extreme weather are important in preventing lightning strike injuries.